The influence of water absorption on unidirectional and 2D woven CFRP composites and their mechanical performance. (1st February 2020) - Almudaihesh, Faisel; Holford, Karen; Pullin, Rhys; Eaton, Mark
Abstract: This paper discusses a key parameter 'fibre architecture' that is believed to play a major part in the performance of CFRP composites when subjected to water absorption. Unidirectional, plain, and twill weave CFRP specimens were immersed in water at 70 °C for 40 days. The condition of the matrix was examined using a Scanning Electron Microscope (SEM). The mechanical properties dominated by the condition of the matrix and interfacial regions such as compression, shear, and impact resistance were assessed for un-aged and aged specimens. A reduction in strength was observed for all aged specimens. However, the observed reduction in strength varies depending on both the fibre architecture used and the specific load case. The largest effect on properties was observed in unidirectional materials, which leads to the recommendation that less conservative safety factors should be used for woven fibre architectures.